(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The present study is aimed at studying the impact of Yoga exercises onthe mental health of the Adults. The sample of the present study consists of100 adults by purposive sampling technique to form two groups viz. Group-I andGroup-II. Group-I constituted the individuals who practice one or more Yogaexercises regularly and Group-II constituted the individuals who do notpractice any Yoga exercises in their day to day life. The mental healthinventory (M.H.I.) developed by Dr. Jagadisha and Dr. AK Srivastava (1983) wasadministered to the two groups to assess their mental health status. It waspredicted that performing Yoga exercises regularly would significantly affectthe mental health of the adults. It was concluded that there is significantdifference between adults of Group-I (who perform Yoga) and adults of Group-II(who do not perform Yoga) with regard to their mental health.